Cryo-EM Structure of Isomeric Molluscan Hemocyanin Triggered by Viral Infection - Zhu, Hongtao (Public Library of Science, 2014)
Hemocyanins (Hcs) of arthropods and mollusks function not only as oxygen transporters, but also as phenoloxidases (POs). In invertebrates, PO is an important component in the innate immune cascade, where it functions as the initiator of melanin synthesis, a pigment involved in encapsulating and killing of pathogenic microbes. Although structures of Hc from several species of invertebrates have been reported, the structural basis for how PO activity is triggered by structural changes of Hc in vivo remains poorly understood. Here, we report a 6.8 Å cryo-electron microscopy (cryo-EM) structure of the isomeric form of hemocyanin, which was isolated from Abalone Shriveling syndrome-associated Virus (AbSV) infected abalone (Halitotis diversicolor), and build a pseudoatomic model of isomeric H. diversicolor hemocyanin 1 (HdH1). Our results show that, compared with native form of HdH1, the architecture of isomeric HdH1 turns into a more relaxed form. The interactions between certain functional units (FUs) present in the native form of Hc either decreased or were totally abolished in the isomeric form of Hc. As a result of that, native state Hc switches to its isomeric form, enabling it to play its role in innate immune responses against invading pathogens.